The birth of Propher Muhammad - Khan,saniyasnain (china goodwordbooks, 2021)
Saniyasnain Khan's books on the Prophet Muhammad (PBUH) aim to introduce young readers to the life and teachings of the Prophet in an engaging and accessible way. These books, often richly illustrated, cover key events from his birth and early life in Mecca, his prophethood and preaching, the challenges faced in Mecca, the migration to Medina, and his later life and teachings. The focus is on presenting the Prophet's life story in a way that is easy for children to understand and appreciate, highlighting the values of patience, compassion, and faith.